PENINGKATAN KEMAMPUAN LITERASI SAINS SISWA KELAS V SDN SIDOREJO 1 TUBAN MELALUI PEMBELAJARAN BERBASIS MASALAH (PBL) - Ifa Seftia Rakhma Widiyanti; Sri Muryantiningsih (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2018)
The objectives of this study were to know the student's response after implementing scientific literacy through problem based learning and its influence on students' scientific literacy ability. This study used the classroom action research formed by Kemmis & Taggart. Implementation problem based learning was conducted to fifth grade SDN Sidorejo 1 Tuban in the academic year 2017/2018. Scientific literacy through problem based learning received good response from students, its above 80% consists of language, graphic, and suitability of technical requirements of teaching materials. The ability of student scientific literacy is enhanced for six indicators, identifying valid scientific opinions, conducting an effective literature, understanding the design elements of the study and how their impact on findings/ conclusions, solving problems using quantitative skills, understanding and interpreting basic statistics, predicting, and conclusing based on quantitative data.